2019
DOI: 10.1101/19002899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Excess weight mediates changes in HDL pool that reduce cholesterol efflux capacity and increase antioxidant activity

Abstract: Objective: Obesity-related decline in high-density lipoprotein (HDL) functions such as cholesterol efflux capacity (CEC) has supported the notion that this lipoprotein dysfunction may contribute for atherogenesis among obese patients. Besides, potentially other HDL protective actions may be affected with weight gain and these changes may occur even before the obesity range. Methods: Lipid profile, body mass index (BMI), biochemical measurements, and carotid intima-media thickness (cIMT) were obtained in this … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…Additionally, we found that HDL was positively associated with total cholesterol and hipline, but negatively associated with body weight, which was not echoed by the evidence that the correlation between HDL and total cholesterol was not significant in Japan and South Korea. [33] In a previously reported study, HDL and hipline were found to be reduced with acupuncture, which indirectly reflected the positively correlation of HDL with hipline, [34] and in another study, increased body weight would impair the protective functions of HDL, [35] and which supported our finding that HDL was negatively associated with body weight.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, we found that HDL was positively associated with total cholesterol and hipline, but negatively associated with body weight, which was not echoed by the evidence that the correlation between HDL and total cholesterol was not significant in Japan and South Korea. [33] In a previously reported study, HDL and hipline were found to be reduced with acupuncture, which indirectly reflected the positively correlation of HDL with hipline, [34] and in another study, increased body weight would impair the protective functions of HDL, [35] and which supported our finding that HDL was negatively associated with body weight.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, BMI was inversely related to HDL-C activity in inhibiting platelet aggregation and cholesterol efflux capacity. Taken together, this study suggested that the increase in BMI was linked to impaired cardioprotective functions of HDL-C and a concomitant increase in atherosclerosis [32]. Furthermore, an inverse correlation between serum HDL-C concentration and stroke has been reported among those with BMI < 24 kg/m 2 ; however, this finding no longer proved true for patients with BMI ≥ 24 kg/m 2 [33].…”
Section: Bmi Modifies the Hdl-c Effect On The Cardiovascular Systemmentioning
confidence: 72%
“…Then, these HepG2 cells were seeded at a density of 5 × 10 5 /well on 2 6-well plates, and grown to 70%-80% confluence for 24 hours before adding the extracted 50 µg/ml of HDL. 7…”
Section: Methodsmentioning
confidence: 99%